Fiqh of Worship in the Context of Modern Life: Adaptation in the Implementation of Prayer in Public Places - Pujiani, Aprita; Rochbani, Ita Tryas Nur (Zabags International Journal of Islamic Studies, 2025)
The implementation of prayer, as one of the pillars of Islam, has specific rules in Islamic jurisprudence (fiqh). However, the development of modern life has posed new challenges in practicing worship, particularly in performing prayers in public spaces. This study aims to analyze the adaptation of fiqh in the context of modernity, with a focus on the performance of prayer in public places. The research method used is literature study with a qualitative-descriptive approach. The results show that fiqh provides flexibility in performing prayer in public spaces, as long as the conditions and pillars of prayer are met. The discussion covers aspects of cleanliness, the direction of the Qibla, and the focus during prayer in public places. The conclusion of this study emphasizes the importance of a dynamic understanding of fiqh to maintain the continuity of worship amidst the demands of modern life. The implications of this study indicate that: (1) Fiqh education should emphasize the flexibility of worship in public spaces; (2) Public facility managers can provide suitable prayer spaces; and (3) Technological innovations, such as Qibla direction apps, can further facilitate the performance of prayer in public spaces.